The influence of essentialist and social constructionist notions on perceptions of “realness”: Implications for LGBTIQ+ experiences - Bartelsx, Mik S.; Le Forestier, Joel M.; Hug, Anton M. O.; Morgenroth, Thekla; Rosello Peñaloza, Miguel Andrés. (John Wiley and Sons, 2024)
Essentialism is an ontological belief that social groups share underlying “essences,” while social constructionism suggests social groups are formed and upheld by cultural understandings. We aim to highlight that essentialist and social constructionist beliefs regarding LGBTIQ+ identities underlie psychological evaluations of whether an LGBTIQ+ identity is real (social recognition of existence). These evaluations have tangible consequences for LGBTIQ+ people such that LGBTIQ+ identities considered real are (de)valued while those considered not real are marginalized. Central to our examination is the concept of “naturalness,” which often affords realness. This is reflected through essentialist thought at the individual level when evaluating the realness of LGBTIQ+ identities. However, while LGBTIQ+ people may embrace essentialist rhetoric to defend their identities as real, many draw instead on social constructionist notions. Lastly, we examine how essentialist and social constructionist rhetoric are evident in structural systems to either deny or legitimize LGBTIQ+ identities as real. By reimagining LGBTIQ+ research, we seek to expand the understanding of these identities.
Keywords: Social construction; Identidad de género; Percepción